Qualidade de sementes de milho colhidas em espigas com alto teor de água e submetidas à secagem com controle da umidade relativa do ar - Ávila, Maria Alice Bento (2021)
In the current agricultural scenario, corn seeds are harvested in advance from the ear with a high water content, which requires a planning of the reception and drying process, which aims to bring the product to an adequate moisture standard with the maintenance of its post-harvest physiological state. harvest. Thus, the objective of the first work was to evaluate drying processes of corn seeds on the cob with different controls and parameters as a function of environmental conditions and drying rates and the relationship with physiological quality. In the second work, the effects of temperature and relative humidity during drying on the physiological and sanitary quality of hybrid corn seeds, harvested on the cob, were verified. For both studies, the simple hybrids BM 709 PRO2 and BM 812 PRO2 were used, harvested in winter and summer seasons, submitted to two methods of stationary drying: the MT, with only temperature control, constant between 38ºC and 40ºC; MUR, with relative humidity control between 25 and 30%, and maximum temperature control at 40°C. The seeds were harvested on the cob at 35% moisture and dried to 11%. The monitoring of drying was carried out by evaluating the drying rate over time and the environmental psychrometric conditions. The seeds were stored in two environments: in a cold and dry chamber at 10ºC and 50% RH; and in a 25C chamber, without relative humidity control. The physiological quality of the seeds was evaluated at the beginning of the storage period and at 4, 8, 12 and 16 months for both studies. The experiment was carried out in a completely randomized design in a 2x2x5 factorial scheme, involving drying methods, environments and storage times, with four replications. In the first work, in summer, the methodology with minimum relative humidity and maximum temperature (MUR) control provides higher drying rates and consequent reduction of drying time, without harming the physiological quality of the seeds. Controlling the relative humidity of the air in the dryers is essential for the drying of corn seeds. It was concluded in the second work that the control of minimum relative humidity, between 25 and 30%, in addition to the control of the maximum temperature of 40°C, during the drying of corn seeds harvested on the cob is favorable to the physiological and sanitary quality of the seeds. seeds during storage. Storage in controlled cold chamber conditions (10ºC and 50% RH) promotes better maintenance of the physiological quality of corn seeds in relation to the climatized environment (25ºC), after 8 months of storage.